Effects of H2O2 Treatment Combined With PI3K Inhibitor and MEK Inhibitor in AGS Cells: Oxidative Stress Outcomes in a Model of Gastric Cancer - Savino, Luca; Di Marcantonio, Maria Carmela; Moscatello, Carmelo; Cotellese, Roberto; Centurione, Lucia; Muraro, Raffaella; Aceto, Gitana Maria; Mincione, Gabriella (Frontiers in Oncology, 2022)
Gastric cancer is worldwide the fifth and third cancer for incidence and mortality, respectively. Stomach wall is daily exposed to oxidative stress and BER system has a key role in the defense from oxidation-induced DNA damage, whilst ErbB receptors have important roles in the pathogenesis of cancer. We used AGS cells as an aggressive gastric carcinoma cell model, treated with H2O2 alone or combined with ErbB signaling pathway inhibitors, to evaluate the effects of oxidative stress in gastric cancer, focusing on the modulation of ErbB signaling pathways and their eventual cross-talk with BER system. We showed that treatment with H2O2 combined with PI3K/AKT and MEK inhibitors influenced cell morphology and resulted in a reduction of cancer cell viability. Migration ability was reduced after H2O2 treatment alone or combined with MEK inhibitor and after PI3K/AKT inhibitor alone. Western blotting analysis showed that oxidative stress stimulated EGFR pathway favoring the MAPKs activation at the expense of PI3K/AKT pathway. Gene expression analysis by RT-qPCR showed ErbB2 and OGG1 increase under oxidative stress conditions. Therefore, we suggest that in AGS cells a pro-oxidant treatment can reduce gastric cancer cell growth and migration via a different modulation of PI3K and MAPKs pathways. Moreover, the observed ErbB2 and OGG1 induction is a cellular response to protect the cells from H2O2-induced cell death. In conclusion, to tailor specific combinations of therapies and to decide which strategy to use, administration of a chemotherapy that increases intracellular ROS to toxic levels, might not only be dependent on the tumor type, but also on the molecular targeting therapy used.